Gender and Geographical Diversity in Authorship, Peer Reviewing, and Editorial Roles in the European Journal of Vascular and Endovascular Surgery Vascular Forum - Melina Vega de Céniga; June Fernández (EJVES Vascular Forum, 2025)
Objective: Gender based disparities have been reported regarding principal investigator positions, authorship of medical published literature, reviewing roles, and representation in journal editorial boards. This study aimed to analyse gender and geographical differences in the authorship and editorial roles of the European Journal of Vascular and Endovascular Surgery Vascular Forum (EJVES VF). Methods: An observational retrospective study was performed of all consecutive submissions to EJVES VF between 2020 – 2023. Data were gathered on: first author's gender, first author's professional country, last author's gender, number of authors per submission, article type, and final editorial decision. Gender and professional country of external reviewers and editorial staff were also analysed, as well as performance indicators. The statistical analysis was descriptive and chi squared and t tests were used. Results: A total of 577 submitted papers were included. First authors were female (FFA) in 26.7% and 28.5% of submitted and accepted papers, and last authors (FLA) in 16.5% and 22%, respectively. The acceptance rate was 34.7% (n = 200), which was similar for FFA and male first authors (37% vs. 33.8%; p = .47). The FLA had a higher acceptance rate than male last authors (46.3% vs. 32.4%; p = 0.009). The acceptance rate of original research and review papers was 34.7% (n = 42), 28.2% (n = 101) for case reports, short reports, editorials, and surgical videos, and 52.2% for images, correspondence, and invited commentaries (p < .001). The highest acceptance rate was achieved by Europe (n = 334; 43.1%), followed by America (n = 68; 33.8%) and Australasia (n = 20; 30%) (p < .001). The journal had six female and ten male editors. The proportion of female reviewers rose from 12.4% in 2020 to 17% in 2023, and female editorial board members from 7% to 21%. Performance indicators were statistically similar for male and female reviewers. Conclusion: Female authorship is under represented in submitted and published papers in EJVES VF, with important geographical differences. The number and percentage of female reviewers is increasing; their performance is comparable with their male colleagues.